PENGATURAN EMISI GAS RUMAH KACA BERDASARKAN PROTOKOL KYOTO DAN IMPLEMENTASINYA DI INDONESIA - Firdaus Muhamad Iqbal; Neni Ruhaeni (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
Climate change is mainly due to increasing concentrations of CO2 and other greenhouse gases. Indonesia has ratified the Kyoto Protocol of 1997 with Undang Undang Nomor 17 Tahun 2004 concerning the Ratification of the Kyoto Protocol To The United Nations Framework Convention On Climate Change. Indonesia is a party of the Kyoto Protocol 1997 and is bound to implement provisions in reducing greenhouse gas emissions in its territory. Based on this phenomenon, the problem in this study is how to regulate greenhouse gas emissions based on the Kyoto Protocol 1997 and how the implementation in Indonesia? The method used in this study is a qualitative method with secondary data sources. The result of this study is to discover the regulation of greenhouse gas emissions according to the Kyoto Protocol 1997 and to determine the implementation of the regulation greenhouse gases based Kyoto Protocol in Indonesia and obstacles towards the implementation.